Sistem Pendukung Keputusan Untuk Pengadaan Fasilitas Hotel Menggunakan Metode TOPSIS - Hendartie, Susi; Surarso, Bayu; Noranita, Beta (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
The development of hotel business to make consumers more critical to choose a hotel products and services. If the hotel facilities more complete, so interest of the consumer is higher to choose the hotel. This  research study intend to build a decision support system for the procurement of hotel facilities with TOPSIS method. This method uses the six alternative form of the data; hotel rooms (guest  room), karaoke, gift shop, a gym, spa and travel corner (travel tour information) and data of some criteria. This method was chosen because it is based on the best alternative concept, was not only has the shortest distance from the positive ideal solution, but also has  the longest distance  from  the  negative  ideal  solution.  TOPSIS  calculations  systems  have  been  done  the  comparison  of  final  value  using  excell calculation. Calculations that used in this research study is simple and produces alternative hotel rooms (guest room) with t he highest ranking as the ideal solution. TOPSIS method facilitates decision-makers in choosing the best alternative for the procurement of hotel facilities.Keywords : Decision support system; Hotel facilities; TOPSIS